A comparison of flight of colours with visually evoked responses in patients with multiple sclerosis. Issue 6 (June 1980) - Swart, S; Millac, P
Abstract : The flight of colours test was performed in a series of patients with multiple sclerosis. Visually evoked responses were then measured in the same patients. The two tests were found to be comparable in their ability to detect disturbance in the visual system.